Digital competency strengthening model, motivation, and innovative work culture to improve performance and the competitiveness of MSMEs in the special economic zone of Palu - Evawarta I. Pagisi; Maulid Sakaria; Abd. Azis (Institute of Computer Science (IOCS), 2026)
This study aims to analyze the influence of digital competencies, motivation, and innovative work culture on the performance of MSMEs in Palu City as an effort to strengthen business competitiveness in the era of digital transformation. The research uses a quantitative approach with a survey method of 150 MSME actors selected through purposive sampling techniques. Data were collected using questionnaires that had met the criteria for validity and reliability, with a Cronbach's Alpha value of 0.853 indicating a high level of reliability. Data analysis was carried out using multiple linear regression. The results of the study produced a regression equation Y = 8.020 – 0.033X? + 0.242X? + 0.353X?. Partially, digital competence had no significant effect on the performance of MSMEs (? = -0.033; t = -0.794; p = 0.428), while motivation had a positive and significant effect (? = 0.242; t = 2.710; p = 0.008) and innovative work culture also had a positive and significant effect (? = 0.353; t = 4.261; p = 0.000). The results of the simultaneous test showed that digital competence, motivation, and innovative work culture together had a significant effect on the performance of MSMEs with values of F = 16.835 and p = 0.000. Multicollinearity testing showed no correlation problems between independent variables with a Tolerance value of 0.709–0.953 and a VIF of 1.050–1.411. The findings of the study indicate that the improvement in the performance of MSMEs is more determined by motivation factors and innovative work culture than by digital competence alone. Therefore, the MSME development strategy needs to be directed at strengthening human resources that not only focus on improving digital skills, but also on forming motivation and work culture that is adaptive, creative, and innovation-oriented to support business sustainability and competitiveness